Synthesis and characterization of mixed ligand chiral nanoclusters. Issue 28 (30th June 2016) - Guven, Zekiye P.; Ustbas, Burcin; Harkness, Kellen M.; Coskun, Hikmet; Joshi, Chakra P.; Besong, Tabot M. D.; Stellacci, Francesco; Bakr, Osman M.; Akbulut, Ozge
Abstract : Chiral mixed ligand silver nanoclusters were synthesized in the presence of a chiral and an achiral ligand. While the chiral ligand led mostly to the formation of nanoparticles, the presence of the achiral ligand drastically increased the yield of nanoclusters with enhanced chiral properties. Abstract : Chiral mixed ligand silver nanoclusters were synthesized in the presence of a chiral and an achiral ligand. While the chiral ligand led mostly to the formation of nanoparticles, the presence of the achiral ligand drastically increased the yield of nanoclusters with enhanced chiral properties.